Rapid gene isolation in barley and wheat by mutant chromosome sequencing. Issue 1 (December 2016) - Sánchez-Martín, Javier; Steuernagel, Burkhard; Ghosh, Sreya; Herren, Gerhard; Hurni, Severine; Adamski, Nikolai; Vrána, Jan; Kubaláková, Marie; Krattinger, Simon; Wicker, Thomas; Doležel, Jaroslav; Keller, Beat; et al.
Abstract Identification of causal mutations in barley and wheat is hampered by their large genomes and suppressed recombination. To overcome these obstacles, we have developed MutChromSeq, a complexity reduction approach based on flow sorting and sequencing of mutant chromosomes, to identify induced mutations by comparison to parental chromosomes. We apply MutChromSeq to six mutants each of the barleyEceriferum-q gene and the wheatPm2 genes. This approach unambiguously identified single candidate genes that were verified by Sanger sequencing of additional mutants. MutChromSeq enables reference-free forward genetics in barley and wheat, thus opening up their pan-genomes to functional genomics.